Pengaruh Model Pembelajaran LOK-R Berbantuan Media Kode Batang terhadap Keterampilan Membaca Cerita fantasi - Neli Agustin; Wika Soviana Devi (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the effect of the LOK-R learning model assisted by bar code media on the ability to read fantasy stories. The research was conducted at SMP Muhammadiyah 19 Sawangan using a sample of 56 students divided into two groups, namely class VII.3 as an experimental group consisting of 28 students and class VII.1 as a control group consisting of 28 students. This research uses quantitative methods (true experiment) with post-test-only research design. The results showed a significant difference between the experimental class that used the LOC-R learning model assisted by bar code media and the control class that did not use the LOC-R learning model assisted by bar code media. Statistical analysis using the t-test formula showed that the sig. (2-tailed) = 0.000 <0.05, and the calculated t- value obtained is 6.756 with df = 54. At the 5% significance level, the t- table value is 1.674.Based on the value of t-count > t-table, Ho is rejected, and Ha is accepted. Therefore, it can be concluded that the application of the LOC-R learning model assisted by bar code media has a significant effect on fantasy story reading skills.